Import and export parity price analyses of selected vegetables and spices in Bangladesh (Bangladesh Journal of Agricultural Research, 2017)
The study was undertaken to find out the export potentialities of selected vegetables and import substitution of selected spices in Bangladesh. Seven hundred twenty vegetables and 320 spices growers, 25 suppliers, and 25 exporters were randomly selected for the study.Net margin analysis was done on both variable and total cost basis. Domestic resource cost (DRC) analysis was also done for estimating comparative advantage of the selected vegetables and spices. The study revealed that net returns were positive for all vegetables and spices producers. However, the highest net return was estimated for brinjal producers (Tk. 273799/ha) followed by bittergourd producers (Tk152145/ha). In the case of spices, the highest net return was received by ginger producers (Tk. 231399/ha) followed by onion producers (Tk. 122308/ha).Comparatively lower net returns were found for okra (Tk51830/ha) and garlic producers (Tk 99352/ha). Vegetables exporters received the highest net margin (Tk32852/ ton) from UK market which was higher than the Middle East market (Tk22869/ton).The highest benefit cost ratio (BCR) was calculated for brinjal (1.9) followed by ash gourd (1.8). For spices, BCR were 2.1and 1.8 for ginger and garlic respectively. Bangladesh had comparative advantage for producing all selected vegetables as the estimates of domestic resource cost (DRC) were less than one. The value of DRC for all selected spices were less than unity implied that the production of these spices would be highly efficient for import substitution. Therefore, the study have been undertaken to find out this issues.Bangladesh J. Agril. Res. 42(2): 321-341, June 2017